Development of Augmented Reality-Based Flashcard Learning Media on Human Respiratory System Materials - Meytania Najwa Putri Azzahra; Aldina Eka Andriani (Jurnal Pijar MIPA, 2026)
Teachers have not been optimal in developing technology-based learning media in the form of interactive games, so that student learning outcomes on human respiratory system materials in elementary schools are still low. This study aims to describe the design, feasibility, and effectiveness of Augmented Reality-based flashcards for improving the learning outcomes of grade V students on the human respiratory system. This research is a Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects amounted to 27 students in class V. Data collection techniques included observation, interviews, questionnaires, documentation, and pretest and posttest assessments. Data were analyzed using normality tests, Paired Sample t-Test, and N-Gain tests. The flashcard media was developed using Canva and integrated with AR technology through the Assemblr Edu platform to support concrete and interactive visualization of concepts. Integrating AR-based flashcards into interactive edugames for elementary students. This Augmented Reality contains explanations of respiratory organs, organ functions, interesting facts, respiratory organ disorders, and human breathing mechanisms. The validation results showed that the media was highly feasible to use, with validation by material experts at 91.07% and by media experts at 95.37%. The responses of teachers and students also showed very positive results with percentages of 96.59% and 90%, respectively. The effectiveness of the media was demonstrated by an increase in the average score from 55.25 on the pretest to 74.25 on the posttest, with a Sig. p-value of < 0.001 and an N-Gain score of 0.4581 in the medium category. The findings of the study show that AR-based flashcards have been successfully developed, are highly feasible, and are effective in improving student learning outcomes, serving as an innovative learning medium that supports engaging and interactive science learning.